Flood Vulnerability Analysis using Weighted Overlay - Ferzha Putra Utama; Yudi Setiawan; Arie Vatresia; Julia Purnama Sari (UIR PRESS, 2022)
Several areas in Bengkulu City are affected by floods every year; one of the worst is the Sungai Serut sub-district. The existence of a river that stretches along Sungai Serut also plays a role in floods over the Bengkulu area. Furthermore, this study to see the priority area over this district is still limited. Mapping flood areas is one way to provide information, especially for decision-makers in flood control using geographic information systems. Our research aims to map flood vulnerability areas based on land height, slope, and river buffer by weighting these criteria. This thematic map is the result of overlaying several maps according to the flood vulnerability criteria. The results of this study indicate that Sungai Serut is an area with